The Malaysian media dependency during COVID-19 crisis - Ezzauddin Hussein, Eliza; Syed Abdullah Idid, Syed Arabi (2021)
The COVID-19 pandemic is a known threat to global health and socio-ecological normalcy. Hence, making it natural for the public to find ways to survive the pandemic and overcome the uncertainties threat. One of the ways is through equipping ourselves with enough information through media exposure and consumption. This is precisely why we could look at the media dependency theory to prove the claims that media become the main sources for the public to look for information and certainties in times of crisis. Specifically, this study aims to identify the Malaysian media platform dependency during COVID-19 and the differences of media platform dependency between races and education level. A total of 1,309 Malaysian respondents of different races and education levels have participated in the survey conducted during the COVID-19 pandemic. The findings suggest that the pattern of media dependency varies according to the nature and background of the society, nature of control and nature or issue of the crisis at the time. Although all respondents reported highly depended on various social media platforms, it was found that there is an obvious difference on the traditional media dependency where the Malays/Bumiputera depends more on TV and Radio whilst the Chinese read and depended on newspapers far more than the other races. There is also a slight frequency difference found on media dependency according to education level where Diploma and Degree holders are more prone to the use of Twitter and Instagram. This study concludes that the media dependency theory can still predict the use of traditional media and social media as it refers to how the media is used by the society to understand the crisis happening surrounding them, as well as to act meaningfully and effectively in society in terms of information sharing and for fantasy and escape. Hence, this theory is still relevant for media study and research. However, to make study on this theory remain relevant, future research can also put focus on the relationship of the theory with the country media system too, not totally focusing on modern dependency only.